Intestinal perforation after intravitreal low dose ranibizumab injection for the treatment of type 1 retinopathy of prematurity: A case report - ÇELİKER ATABERK, HANDE; KARADENİZ CERİT, KIVILCIM; ÖZDEMİR, HÜLYA; BİLGEN, HÜLYA SELVA; ÖZEK, EREN; MEMİŞOĞLU, ASLI (My University, 2022)
Purpose To report a newborn patient with gastrointestinal (GIS) perforation after intravitreal ranibizumab (RBZ) treatment. Case report The patient was born at 31 gestational week and hospitalized with the diagnosis of small for gestational age and prematurity. In the follow up he underwent GIS surgery due to necrotizing enterocolitis (NEC) and was diagnosed with retinopathy of prematurity (ROP). At 43 weeks of postmenstrual age, he developed intestinal perforation after 12 h of the second low-dose RBZ injection. According to our knowledge, this is the first report of GIS perforation due to low-dose intravitreal RBZ treatment in an infant with severe ROP. Conclusion The risk of GIS perforation should be taken into consideration during the application of intravitreal vascular endothelial growth factor antagonist agents, especially in newborns with previous GIS surgery and a history of NEC, and these patients should be carefully monitored for GIS complications.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Medicine; Health Sciences; Surgery Medicine Sciences; Eye Diseases and Surgery; GÖZ HASTALIKLARI; Klinik Tıp; Klinik Tıp (MED); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Oftalmoloji; Optometri; Ophthalmology; Optometry; Gastrointestinal perforation; necrotizing enterocolitis; newborn; ranibizumab; retinopathy of prematurity; EFFICACY